2017
DOI: 10.1136/heartjnl-2017-311430
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardiac defibrillator and mortality in non-ischaemic cardiomyopathy: an updated meta-analysis

Abstract: Primary prevention ICD therapy reduces all-cause and cardiovascular mortality and sudden cardiac death in patients with non-ischaemic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
0
14
0
3
Order By: Relevance
“…The baseline risk of SCD in patients with non‐ischemic cardiomyopathy is 1.5% at 1 year and 9% at 5 years; and 5%‐9% at 1 year and 10%‐20% at 5 years in ischemic cardiomyopathy . These risks resulted in studies informing guidelines for ICD use as either primary or secondary prevention of SCD . In this study, we report a risk of SCD at two years after transplant of 0.74% in patients with history of treated rejection, and of 2.4% in patients with treated rejection within 2 years of diagnosis of CAV.…”
Section: Discussionmentioning
confidence: 69%
“…The baseline risk of SCD in patients with non‐ischemic cardiomyopathy is 1.5% at 1 year and 9% at 5 years; and 5%‐9% at 1 year and 10%‐20% at 5 years in ischemic cardiomyopathy . These risks resulted in studies informing guidelines for ICD use as either primary or secondary prevention of SCD . In this study, we report a risk of SCD at two years after transplant of 0.74% in patients with history of treated rejection, and of 2.4% in patients with treated rejection within 2 years of diagnosis of CAV.…”
Section: Discussionmentioning
confidence: 69%
“…(19) To date, to the best of our knowledge, no single randomised controlled trial of ICD therapy in patients with DCM has demonstrated statistically significant reduction in overall mortality, although significant reduction in arrhythmic mortality was seen in the DEFINITE and the recently completed DANISH studies. (20)(21)(22) However, in an updated meta-analysis of primary prevention studies that included DANISH, ICD implantation was still associated with a 23% reduction of all-cause mortality. (23) This was in contrast to the more convincing all-cause mortality reduction seen in primary prevention ICD trials enrolling patients with ischaemic cardiomyopathy.…”
Section: Methodsmentioning
confidence: 99%
“…A recently published, but underpowered, RCT showed no significant reduction in mortality in non-ischaemic cardiomyopathy 7. However, after conducting a meta-analysis, it was evident that the use of ICDs significantly reduced the risk of mortality in patients with systolic dysfunction and non-ischaemic cardiomyopathy8 (figure 1). …”
Section: Examples Of Recent Meta-analysis Impacting Guideline Recommementioning
confidence: 99%